Managing diminished irrigation capacity with preseason irrigation and plant density for corn production - Schlegel, Alan J.; Stone, Loyd R.; Dumler, Troy J.; Lamm, Freddie R. (My University, 2012)
Many of the irrigation systems today in the U.S. Central Great Plains no longer have the capacity to match peak irrigation needs during the summer and must rely on soil water reserves to buffer the crop from water stress. Considerable research was conducted on preseason irrigation in the U.S. Great Plains region during the 1980s and 1990s. In general, the conclusions were that in-season irrigation was more beneficial than preseason irrigation and that preseason irrigation was often not warranted. The objective of this study was to determine whether preseason irrigation would be profitable with today’s lower-capacity groundwater wells at different levels of corn plant density. A field study was conducted at the Kansas State University Southwest Research-Extension Center near Tribune, Kansas, from 2006 to 2009. The study was a factorial design of preseason irrigation (0 and 75 mm), irrigation capacities (2.5, 3.8, and 5.0 mm d[superscript]-1), and plant density (56,000, 68,000, and 80,000 plants ha[superscript]-1). Preseason irrigation increased grain yields an average of 1.0 Mg ha[superscript]-1. Grain yields were 28% greater when irrigation capacity was increased from 2.5 to 5.0 mm d[superscript]-1. Crop water productivity was not significantly affected by irrigation capacity or preseason irrigation. Preseason irrigation was profitable at all irrigation capacities, although only slightly profitable at the highest irrigation capacity. Therefore, it may not be prudent to preseason irrigate with irrigation capacities of 5.0 mm d[superscript]-1 or greater so that the water can be conserved for later use. At irrigation capacities of 2.5 and 3.8 mm d[superscript]-1, a seeding rate of 68,000 seeds ha[superscript]-1 was generally more profitable than lower or higher seeding rates. A higher seeding rate (80,000 seeds ha[superscript]-1) increased profitability when irrigation capacity was increased to 5.0 mm d[superscript]-1.
Citation: Transactions of the ASABE. 55(2): 525-531. (doi: 10.13031/2013.41394) @2012
Keywords: Corn; Irrigation capacity; Irrigation management; Preseason irrigation